The Diversity of Diseases Affecting Long Beans (Vigna sinensis L.) in the Banyuasin Region (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2026)
Long bean (Vigna sinensis L.) is a widely cultivated legume in Indonesia, offering significant economic potential due to its ease of cultivation. However, its productivity is often hampered by major pathogens like Uromyces appendiculatus, which causes rust disease, and various mosaic viruses. Rust disease manifests as small brown powdery spots on leaves, while viral infections can severely reduce or even eliminate fresh pod yields. This field study aimed to identify the primary diseases affecting long beans, determine their causative agents, and distinguish their specific symptoms. The research employed a survey method through purposive sampling on farmers' land. Observations were conducted across several different plots using a diagonal sampling technique at multiple points to collect plant samples. The results indicated that both fungal rust and viral mosaic are the predominant diseases impacting local crops. This inventory provides essential data for farmers to better recognize and differentiate symptoms, ultimately supporting more effective disease management and safeguarding the economic value of long bean production in the region.